E-module innovation as a learning solution for chemistry course during the pandemic based on problem-based learning - Devi Ayu Septiani; Anak Agung Ayu Trisna Handayani; Hermansyah Hermansyah; Abdul Syukur; Jamaluddin Jamaluddin (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2021)
Chemistry e-modules based on Problem-Based Learning (PBL) are teaching materials based on electronic learning models or e-learning as a solution during the Covid-19 pandemic for students to learn independently. The purpose of this study is to assess PBL-based academic e-modules from the aspect of validity and feasibility in achieving its learning objectives. The approach used is development research according to the Thiagarajan model. The results showed that at the define stage, an analysis was conducted on the Curriculum 13 (K13) module of the Ministry of Education and Culture (Kemendikbud) with the material Ã¢â¬Åchemical bondingÃ¢â¬Â of Grade X at SMAN 3 Lembar.ÃÂ Furthermore, a module designed using an electronic display integrated with the PBL model was done at the design stage. Meanwhile, the expert validation result obtained an average of 0.86, categorized as valid and feasible criteria at the development stage. The result of studentsÃ¢â¬â¢ responses obtained 72.73% (good criteria), and the result of the chemistry teachersÃ¢â¬â¢ responses obtained 88.06% (very good criteria). The PBL-based Chemistry e-module on chemical bonding material is feasible as a Chemistry learning solution for Class X of SMAN 3 Lembar.